Bottom-up fabrication of FeSb2 nanowires on crystalline GaAs substrates with ion-induced pre-patterning - Weinert, Tom; Hübner, René; Facsko, Stefan; Erb, Denise J. (Frontiers in Physics, 2023)
Most industrial processes are generating waste heat that can be converted into electrical energy with thermoelectric generators (TEGs). For efficient energy harvesting, it is necessary to significantly improve the properties like Seebeck coefficient, electrical and thermal conductivity of the thermoelectric materials in the TEGs. One promising approach are thermoelectric nanostructures to reduce the thermal conductivity while maintaining constant electrical conductivity and Seebeck coefficient. For that reason, this study investigated the possibility of preparing nanowires of the thermoelectric material iron antimonide (FeSb2) on crystalline gallium arsenide GaAs(001) substrates with ion-induced surface nanopatterning. The GaAs(001) substrates were pre-patterned using 1 keV Ar+ ion irradiation. By using an ion source with a broad, unfocused ion beam at normal incidence, the patterned area can be scaled to nearly any size. The self-organized surface structure is formed by reverse epitaxy and is characterized by almost perfectly parallel-aligned ripples at the nanometer scale. For the fabrication of FeSb2 nanowires, iron and antimony were successively deposited on the prepatterned GaAs substrates at grazing incidence and then annealed. They were characterized using transmission electron microscopy (TEM), in particular high-resolution TEM imaging for structure analysis and spectrum imaging analysis based on energy-dispersive X-ray spectroscopy for element characterization. With the presented fabrication method, FeSb2 nanowires were produced successfully on GaAs(001) substrates with an ion-induced nanopatterned surface. The nanowires have a polycristalline structure and a cross-sectional area which is scalable up to 22×22nm2. Due to the highly ordered nanostructure of the GaAs substrates, the nanowires have a length of several micrometer. These bottom-up nanofabrication based on ion-induced patterning can be a viable alternative to top-down procedures regarding to efficiency and costs.